Design and characterization of a novel biocorrodible iron-based drug-eluting coronary scaffold. (5th February 2016) - Lin, Wen-Jiao; Zhang, De-Yuan; Zhang, Gui; Sun, Hong-Tao; Qi, Hai-Ping; Chen, Li-Ping; Liu, Zi-Qiang; Gao, Run-Lin; Zheng, Wei
Abstract: Long corrosion period and slow resorption in vivo remain major limitations for iron-based bioresorbable scaffolds. This work focused on the design and characterization of a novel iron-based drug-eluting coronary scaffold (IBS scaffold) made of nitrided iron materials. The 53 μm IBS scaffold shows good device performance comparable to a current mainstream drug-eluting coronary stent (Xience Prime™) due to the good comprehensive mechanical performance of nitrided iron materials. The novel design of a zinc barrier layer makes it possible for the IBS scaffold to have ultrathin struts and thick PDLLA coating of 12 μm to maintain adequate scaffolding (125 kPa) after 3 months implantation while having a significantly shortened corrosion period (13 months). The biocorrosion and bioresorption of the IBS scaffold could be effectively evaluated using Micro-CT, OCT and MRI methods. Although complete bioresorption of the corrosion products has not been observed yet, there are no identified biological problems for the IBS scaffold after implantation in rabbit abdominal aorta up to 13 months. This study demonstrates that the IBS scaffold with novel design has significantly shortened corrosion period and less amount of corrosion products without causing any biological problems after implantation up to 13 months, therefore is promising for coronary application. Graphical abstract: Highlights: A PDLLA coating was successfully designed to accelerate corrosion of the iron-based scaffold with corrosion period significantly shortened to 13 months. A zinc barrier layer was successfully designed to put off the onset of corrosion of the iron-based scaffold to maintain structural integrity and adequate scaffolding to the lesion vessel wall after 3 months implantation. Nitrided iron and zinc barrier layer make it possible to design an ultrathin (53 μm) iron-based scaffold with device performance comparable to a mainstream Co-Cr stent and reduced amount of nitrided iron and therefore less corrosion products to shorten the bioresorption time in vivo. Micro-CT, OCT and MRI were demonstrated to be effective methods to follow up biocorrosion and bioresorption of the iron-based scaffold.